Survey of the ancient world - Breasted, James Henry (Ginn and company, 1919)
The Greek Conquest of the gean World and The Age of the Greek Kings; The Coming of the Greeks; The Nomad Greeks make the Transition to the Settled Life; Greek Civilization in the Age of the Kings; The Age Of The Nobles And Greek Expansion In The Mediterranean; The Disappearance of the Kings and the Leadership of the Nobles; Greek Expansion in the Age of the Nobles; Greek Civilization in the Age of the Nobles; The Industrial Revolution And The Age Of The Tyrants; The Industrial and Commercial Revolution; Rise of the Democracy and the Age of the Tyrants; Civilization in the Age of the Tyrants; The Repulse Of Persia And The Rise Of The Athenian Empire; The Coming of the Persians; The Greek Repulse of Persians and Phoenicians; The Rivalry with Sparta and the Rise of the Athenian Empire; Athens In The Age Of Pericles; The Home, Education, and Training of Young Citizens; Higher Education, Science, and the Training gained by State Service; Art and Literature; The Fall Of The Athenian Empire; The Second Peloponnesian War; Third Peloponnesian War and Destruction of the Athenian Empire; The Final Conflicts Among The Greek States And Their Higher Life After Pericles; Spartan Leadership and the Decline of Democracy; The Fall of Sparta and the Leadership of Thebes; Architecture, Sculpture, and Painting; Religion, Literature, and Thought